Occurrence of linguacultural terms in English and Uzbek folk tales - Usmonova Sevara Sultanovna; Raximova Charosxon Baxromjon qizi (Periodica Journal, 2023)
It would not be an embellishment to say that folklore traditions connect people and nations through invisible lines. One can see the connectivity as the integrity of intimacy, solidarity and mutual understanding among nations of the world. Roaming the fairy tales orally among people entire the world as a form of that solidarity caused them to become an inseparable part of every nation ‘s folklore traditions. Therefore, studying fairy tales of nations from a theoretical, cultural and philosophical point of view, comparing and identifying the similar and differential lines can be the continuous work of mutual understanding between folks in the world. The author of this article dealing with the issue of cumulative tales intended: To review the previous theoretical researches about the cumulative issue in the fairy tales; To identify how the presented approaches of the scholars apply to the Uzbek and English cumulative tales; To identify and compare the pure cumulative structure in the Uzbek and English fairy tales; It is important to mention that a larger part of researches about cumulative tales belongs to Russian scholars. Accounting lack of researches about Uzbek cumulative tales caused to make the work more perspective and relating it with English cumulative fairy tales can help to understand the issue deeply. Based on the approaches of Archer Taylor, Stith Thompson, V.Propp, I.Kruk, I.Amroyan, A.Kreatov, J.Eshonkulov, and Sh. Turdimov, we analyzed two nations‘ cumulative fairy tales and tried to identify the fairy tales among Uzbek and English fairy tale fond which can present a pure cumulative structure. The English cumulative tales Teeny Tiny, The Old Woman and Her Pig, Henny-Penny How Jack Seeks his Fortune and the Uzbek cumulative tales Susambil ,The Egg and The Kidney, The Three Goats‖ can present the reader a good perception about the accumulation in fairy tales. Studying Uzbek and English cumulative tales comparatively is significant for further researches of other nations‘ cumulative tales
Keywords: studies; cumulative fairy tales; cumulative issue; chain links